A alienação em Lukács: fundamentos para o entendimento do complexo da educação - Lima, Marteana Ferreira de (2014)
The present thesis, based upon the Marxian-Lukacsian frame of reference, in an ontological perspective, aims to examine the complex of alienation in Lukács and its relation to education. Taking into account the changes that such complex undertakes throughout Lukács work, it performs a critical-comparative study of the alienation concept as it presents itself in History and Class Consciousness and Ontology of Social Being, from the standpoint that the anatomy of alienation in the work of maturity reveals itself as the key to understanding the anatomy of alienation formulated by the author in his youth. In order to clarify the theoretical and practical fundamentals that distinguish the two conceptions systematized by the author, taking as guideline, his road to Marx, it retrieves his trajectory, highlighting the existence of three key moments in his relationship with Marxism, corresponding to the pre-marxist, the protomarxist and the Marxist periods. In view of the dialectic relationship of continuity in the discontinuity, and discontinuity in the continuity, inherent to Lukács trajectory, it searches for a line of continuity between the two works mentioned above, by examining its central categories. From the point of view of education as a universal social complex, characterized by an ontological dependence and relative autonomy rapport with the labor complex, it seeks to highlight its connections to the alienation complex, pinpointing, in a more particular way, its limits and possibilities in overcoming alienation.